Should an R&D manager refer to distant technical fields? The effectiveness of new combinations with knowledge from different technical fields through the quantitative analysis of patent data related to NetZero - Hirose, Masayuki (Frontiers in Research Metrics and Analytics, 2023)
This work showcases a technique to categorize NetZero-related patent applications into three technical fields according to the degree of proximity between claimed invention and cited inventions by comparing technological classifications between the patent applications and cited applications thereof. In showing this method, the author explains the modified method proposed by the author as well as the existing methods shown in previous studies. The proposed method is different from those of previous studies in that it is characterized by comparing the technical fields of not only the primary classification but also the subsequent classifications. This is made possible by using two patent classifications without having a specific classification corresponding to the middle hierarchy in between, rather than using three patent classifications with different hierarchies. This method reduces the possibility that two applications, even if they are the same in their subsequent classification, will be judged as applications in different technical fields because they are in different classes in the primary classification. Using the proposed method, the author examined the impact on subsequent patent application of NetZero-related patent applications filed in Japan. As a result of the analysis, the author found that approximately 70% of subject applications, whose technical field differs from the backward citations when comparing the primary classification only, match one of the subsequent classifications when comparing them in consideration of the subsequent classifications as well. The author then found that these 70% of subject applications had a greater impact on subsequent patent applications than the remaining 30%. (248 words)